Process systems engineering for biofuels development - Bonilla-Petriciolet, Adrian; Rangaiah, Gade Pandu (Wiley series in renewable resources., 2020)
"This is the first book specifically devoted to process systems engineering for the production of biofuels. It covers a wide range of topics associated with the process engineering of biofuels production, including thermodynamic modeling, process design and control, reaction engineering, separation and purification of biofuels obtained from different processing routes and feedstocks. The book is divided into two Parts; Part One begins with an overview of the subject and covers biomass feedstocks, process dynamics and plantwide control of downstream processing in biofuels production, multiscale analysis of bioresources, challenges in modeling thermodynamic properties and phase equilibrium calculations, adsorption processes and bioethanol recovery. Part Two deals with the production and separation of biofuels and addresses computer-aided design, enzyme-catalyzed biodiesel production, process analysis of biodiesel production (including kinetic modeling and simulation) and the use of ultrasonification in biodiesel production, as well as thermochemical processes for biofuel transformation and production of alternative biofuels. This book will provide researchers and postgraduate students with an overview of the recent developments and applications of state-of-the-art technologies and process systems engineering for biofuels production. It will be a useful resource for researchers in renewable energies and practitioners working on biofuels production"--